Multifunctional Oxide-Based Materials: From Synthesis to Application - Jesionowski, Teofil (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The book deals with novel aspects and perspectives in metal oxide and hybrid material fabrication.